2018
DOI: 10.1371/journal.pone.0208306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pequi (Caryocar brasiliense) and juçara (Euterpe edulis) waste extract on oxidation process stability in broiler meat treated by UV-C

Abstract: The aim of this study was to determine the potential for waste extracts from the pequi (Caryocar brasiliense) and juçara (Euterpe edulis) to reduce oxidatiove processes in antibiotic-free broiler meat. The use of natural antioxidants extracted from fruit-processing wastes has been neglected. Although these residues contain high amounts of these bioactive compounds, they are often discarded by industry. Meat samples were exposed previously submitted to UV-C radiation at 1.161 mW / cm2 for 10 minutes to accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…There was no difference ( P > 0.05) in moisture and lipid content among treatments, indicating a successful fat standardization from the addition of skin and abdominal fat ( Table 2 ). Similarly, Frasao et al (2018) also observed no difference in these parameters. In contrast, the conventional broiler meat presented higher ( P < 0.05) values for protein and ash contents than the antibiotic-free broiler meat.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…There was no difference ( P > 0.05) in moisture and lipid content among treatments, indicating a successful fat standardization from the addition of skin and abdominal fat ( Table 2 ). Similarly, Frasao et al (2018) also observed no difference in these parameters. In contrast, the conventional broiler meat presented higher ( P < 0.05) values for protein and ash contents than the antibiotic-free broiler meat.…”
Section: Resultsmentioning
confidence: 79%
“…Regarding the first day of storage (d 0), TPC and TFC values were similar ( P > 0,05) for all treatments. However, the treatments with juçara fruit waste extract addition (AFBEP, AFBEA, CBEP, CBEA) presented the highest ( P < 0.05) TAC and TTC values, certainly related to juçara high content of anthocyanins and tannins ( Frasao et al, 2017 , 2018 ). Moreover, although TTC was also high in treatments with BHT (AFBPC, CBPC), we cannot precisely explain these values.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The antibacterial activity of ultraviolet‐C (UV‐C) is related to induction of the formation of cyclobutene‐fused dimers between adjacent pyrimidine bases (Butot et al ). Moreover, because their action is carried out directly on microbial DNA, food products preserve their sensory characteristics such as colour and pH (Frasao et al ). In addition, the technique has other advantages, such as low cost, easy handling and the absence of irritant by‐products (Butot et al ).…”
Section: Introductionmentioning
confidence: 99%